Effects of School Physical Activity Intervention Programs - Avgerinos Ανδρέας Γ.; Zetou Ελένη; Vernadakis Νικόλαος (Inquiries in Physical Education and Sport, 2006)
It is well established that physical inactivity has detrimental effects on health. Thus, last years the promotion of an active lifestyle is a central focus for the prevention agenda in health bodies worldwide. School is perhaps the most promising environment for the effective promotion of physical activity (PA) in youth. This paper reviews school PA intervention programmes among elementary through high school aged persons. The aim of the paper is to determine the main characteristics and the effectiveness of these interventions. A number of studies from 1980 to 2001 testing PA interventions in school setting were identified by reference lists of published reviews and computerized search methods. The studies reviewed fulfilled the following criteria: i) used a quantitative assessment of PA, ii) included participants who were preschool through middle school age, iii) used a comparison or control group, iv) conducted internationally and in Greece, and v) published in English or Greek language. Significance of effects was examined overall and for various types of interventions. Fifteen studies were reviewed, 13 conducted internationally and two in Greece. Studies showing the best results used strong research designs (randomized), valid and reliable measurements, and multi-dimensional intervention components. Some follow-up results showed PA was sustained in the experimental groups after intervention ended. The collection of school studies is limited for children aged of 9-yrs-old. The most is know about secondary school students. A number of older studies had some weaknesses in the assessment of the dependent variables; more recant studies revealed important novelties in research designs as well as in PA measurement. From this review revealed that: a) special attention is needed for girls at all ages and middle-school aged youth, b) more objective assessment are needed for measuring PA, and c) more studies is needed for younger children.